Boganmeldelser - Kjersti Ericsson; Hans Henrik Brydensholt; Monika Płatek; Paul Larsson; Kerstin Berglund; Mads Bryde Andersen; Gorm Gabrielsen; Thorkild Høyer; Anette Storgaard; Nils Christie; Nils Jareborg; Peter Garde; et al. (Nordisk Tidsskrift for Kriminalvidenskab)
Intet resumé